Os Argumentos Da Existência De Deus À Luz Da Filosofia De Paul Tillich - Emilio, Guilherme Estevam [UNIFESP] (2018)
This Thesis Examines Paul Tillich"S Writings About The Arguments For The Existence Of God. In The Set Of The Systematic Theology They Are Inserted At The Final Of The Analysis Of The Finitude Of The Being, That Is, In The Part Which Deals With The Question For The Meaning Of Being. The Systematic Theology Is Draw From The Author"S Correlation Method, Which Con-Sists Of The Elaboration Of Existential Philosophical Questions And Symbolic Theological An-Swers. One Of The Objectives Of This Method Is To Dialectically Overcome The Natural Theology And The Supranatural One, Aiming At A New Theological Approach. Thus, Once The Author Situ-Ates The Arguments In The Question Context, It Is Already Taken For Granted In The Structure Of The Text That Their Function Is To Establish The Question For The Meaning Of Being, That Is, To Describe The Structure Of Being And Demonstrate Its Finitude From The Analysis Of Its Concepts. This Way, It Is From This Structure - The Constitution Of The Finite Being - That The Arguments